2015
DOI: 10.1370/afm.1804
|View full text |Cite
|
Sign up to set email alerts
|

What Peer Mentoring Adds to Already Good Patient Care: Implementing the Carpeta Roja Peer Mentoring Program in a Well-Resourced Health Care System

Abstract: PURPOSE The purpose of this study was to evaluate the impact of a peer support program on the health outcomes of patients already receiving well-organized, comprehensive diabetes care. METHODS We used a mixed-methods, nonrandomized, control-group design to evaluate the impact of a peer-mentoring program on the health outcomes and self-management behaviors of adults with type 2 diabetes in 15 primary care practices in San Antonio. Propensity score analysis, t-tests, and multivariable repeated analyses were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…Key findings curated by Peers for Progress and reported by papers in this supplement [35][36][37][38][39][40][41] help to guide these efforts.…”
Section: Scaling Upmentioning
confidence: 99%
See 2 more Smart Citations
“…Key findings curated by Peers for Progress and reported by papers in this supplement [35][36][37][38][39][40][41] help to guide these efforts.…”
Section: Scaling Upmentioning
confidence: 99%
“…After its own initial appraisal of 15 sites, Texas-based WellMed extended its peer support program to all 23 of the clinical sites in its network. 36 In Clínicas de Salud del Pueblo in southern California, the Puentes hacia una major vida program for adults with diabetes was used as a model for addressing childhood obesity and helped to guide changes to the clinics' system of care, including provider training and EHR changes to ensure documentation of peer support.…”
Section: S4mentioning
confidence: 99%
See 1 more Smart Citation
“…Peer mentorship can help establish connections among individuals with relatable experiences and positively impact patients’ adjustment to living with chronic disease. 27 , 28 Formalized peer support may improve goal setting, decision making, and self-management for those on or nearing dialysis. 29 However, in the absence of opportunities for peer interaction for those with nondialysis CKD, patients in our study identified research engagement as a way of addressing their perceived lack of community.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly those projects conducted in populations with better access to either privately or publicly funded health care did not appear to benefit significantly with respect to clinical health outcomes from additional peer support [11, 15, 22]. …”
Section: Discussionmentioning
confidence: 99%